Peran Audit Internal Dalam Good Corporate Governance Bank Syariah Di Indonesia - Rito, Rito; Azzahra, Fathimah (Agregat: Jurnal Ekonomi dan Bisnis, 2018)
This paper aims to discover the implementation of GCG in Islamic banksâ, structural analysis of Islamic banksâ internal audit, and the role of internal audit in the GCG implementation of Indonesiaâs Islamic banks. This type of study is qualitative descriptive method by using literature studies. The result shows that banks, which are the top banks in term of asset; BSM, BMI, BNIS and BRIS, have implemented GCG really well. The structure of internal audit in the banks is effective by placing internal audit under the main director/commisaris/others. Generally, the role of internal audit in the banks are; investigating work unit, monitoring the audit findings, evaluating the audit finding, reporting any non-sharia compliance activities, and doing internal control either by whistleblowing system or SPI in each banks according to their needs.